Rola bezpośrednich inwestycji zagranicznych w kształtowaniu profilu gospodarczego województwa podkarpackiego - Puchalska, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The effects of FDI inflows to the region are the subject of many theoretical considerations, both quantitative and qualitative. In the context of shaping the competitiveness of the region receiving capital effects can be both positive and negative. Whether the positive effects predominate in the region over the negative results depends on the possibilities inherent in the region. SubcarpathianVoivodship, despite the weak notes in the rankings of investment attractiveness has its economic profile. It is the aerospace industry, but also electrical engineering, biotechnology, IT and chemical industries. The region has a large concentration of companies especially the aviation industry, research centers and developed educational and training facilities.
Keywords: direct investment; FDI; profile; region